Effect of polyaspartic acid on the setting time and mechanical properties of α-hemihydrate gypsum. (10th April 2023) - Fang, Zhenzhen; Gao, Wenqi; Ai, Hongqi; Pei, Meishan; Guo, Wenjuan; Wang, Luyan
Highlights: PASP is a biodegradable protein-based retarder. PASP has less strength loss compared with previous retarders. PASP prolongs the dissolution of α-HH and crystallization process of gypsum. The conformation of PASP affects the interaction between PASP and Ca 2+ in calcium sulfate solution. Abstract: Polyaspartic acid (PASP) was an environment-friendly and biodegradable polymer, with a protein-like structure composed of L-aspartic acid residues. In this work, PASP with different molecular weights (2000, 4000–5000 and 6000–8000) was utilized as the retarder for α-hemihydrate gypsum (α-HH), and the effect of PASP on the coagulation, hydration and crystallization process of gypsum were investigated. Results showed that the addition of PASP with a low dosage of 0.01% efficiently delayed the hydration of α-HH and prolonged the setting process. Among three polyaspartic acids, PASP with molecular weight of 4000–5000 (PASP 4–5) exhibited the best performance not only in postponing the setting time to 95 min, but also in decreasing the negative impact of retarder on the strength of gypsum. Significantly, the slightest loss of 2.65% in compressive strength was obtained here when compared with other retarders previously reported, under the lowest dosage of 0.01% PASP 4–5. Consequently, the effect of PASP chain length on the retardation of α-HH was analyzed in detail. The conductivity, heat of hydration, X-ray diffraction (XRD), EDTA titration method and scanning electron microscopy (SEM) characterization found that PASP prevented the dissolution of α-HH. Total organic carbon analyzer (TOC) and X-ray photoelectron spectroscopy (XPS) measurements showed that the carboxyl groups of PASP adsorbed on the surface of α-HH to hinder the dissolution of α-HH. The molecular dynamic simulation of PASP further exhibited that three kinds of PASPs presented different conformations in supersaturated calcium sulfate solution due to the interaction between PASP and Ca 2+ ions, and affected their solvent accessible surface area (SASA). In particular PASP 4–5 exhibited the smallest SASA and the strongest interaction with Ca 2+ ions, causing the longest setting time of α-HH.